Entrepreneurial Market Orientation and Marketing Performance: An Evidence from Malang Soybean Cracker Industry - Ananda Sabil Hussein (Jurnal Sosial Humaniora, 2019)
This study aims to test the effect of entrepreneurial marketorientation (EMO) as the development of entrepreneurial orientation concept.Particularly, this study tested the dimensions of EMO, namely innovation,customer orientation, market orientation and entrepreneurial orientation onmarketing performance. To answer the proposed research objectives, thisstudy applied multiple regression analysis. Self-administered questionnaireswere distributed to one hundred respondents and only 67 questionnaires werecollected. The results of multiple regression showed that innovation has apositive significant effect on marketing performance. Similar to innovation,this study indicated that customer orientation has a positive significant effecton marketing performance. As proposed in the hypothesis, this study foundthat market orientation positively affects marketing orientation.Entrepreneurial orientation as the dimension of EMO shows a significanteffect on marketing performance. After the completion of this study, boththeoretical and practical contribution are provided.